Compartmentalized Reconstitution of Post-squalene Pathway for 7-Dehydrocholesterol Overproduction in Saccharomyces cerevisiae - Guo, Xiao-Jing; Yao, Ming-Dong; Xiao, Wen-Hai; Wang, Ying; Zhao, Guang-Rong; Yuan, Ying-Jin (Frontiers in Microbiology, 2021)
7-dehydrocholesterol (7-DHC) is the direct precursor to manufacture Vitamin D3. Our previous study has achieved 7-DHC synthesis in Saccharomyces cerevisiae based on endogenous post-squalene pathway. However, the distribution of post-squalene enzymes between endoplasmic reticulum (ER) and lipid bodies (LD) might raise difficulties for ERG-proteins to catalyze and deliver sterol intermediates, resulting in unbalanced metabolic flow and low product yield. Herein, we intended to rearrange the subcellular location of post-squalene enzymes to alleviate metabolic bottleneck and boost 7-DHC production. After identifying the location of DHCR24 (C-24 reductase, the only heterologous protein for 7-DHC biosynthesis) on ER, all the ER-located enzymes were grouped into four modules as ERG1/11/24, ERG25/26/27, ERG2/3, and DHCR24. These modules attempted to be overexpressed either on ER or on LDs. As a result, expression of LD-targeted DHCR24 and ER-located ERG1/11/24 could promote the conversion efficiency among the sterol intermediates to 7-DHC, while locating module ERG2/3 into LDs improved the whole metabolic flux of post-squalene pathway. Co-expressing LD-targeted ERG2/3 and DHCR24 (generating strain SyBE_Sc01250035) improved 7-DHC production from 187.7 mg/L to 308.2 mg/L at shake-flask level. Further expressing ER-targeted module ERG1/11/24 in strain SyBE_Sc01250035 dramatically reduced squalene accumulation from 620.2 mg/L to the lowest level (by 93.8%) as well as improved 7-DHC production to the highest level (to 342.2 mg/L). Then targeting module ERG25/26/27 to LDs further increased 7-DHC titer to 360.6 mg/L, which is the highest shake-flask level production for 7-DHC ever reported. Our study not only proposes and further proves the concept of pathway compartmentalized reconstitution to regulate metabolic flux, but also provides a promising chassis to produce other steroidal compounds through post-squalene pathway.